Yeni Medyada Haber Dili (Ayşe Paşalı Olayı Üzerinden Geleneksel Medya Ve İnternet Haberciliği Karşılaştırması) - Yurdigül, Yusuf; Zinderen, İ. Etem (The Turkish Online Journal of Design Art and Communication, 2012)
The news subject is the primary subject emphasized diligently by the media studies. The news, which develops and transforms the knowledge and interest of the society, and which recreate the reality according to structure, technology and the ideology of media organizations, has been the guarantee of reliability of the media organizations most of the time, as well as their quality and prestige. Whether be it traditional media or the social media, the language used in the text of a news story is indispensable in terms of the credibility of the news, although it's claimed that the image used defends any event or idea, and the language is only a complementary element. The Ayse Pasali murder, which occupies Turkey's agenda over the news on the violence against women, was chosen as the case study to illustrate the differences in the news language used in the traditional and social media. The news covered in newspapers and Internet news sites on the Ayse Pasali murder will be examined by the comparative content analysis method, and the differences on news languages will be put forward.
Keywords: News; News Language; Social Media; Traditional Media; Haber; Haber Dili; Sosyal Medya; Geleneksel Medya